A Seat at the Table: Academic Librarian Participation on Canadian University Faculty Association Executive and Collective Bargaining Teams - Pash, Anthony; Patterson, Erin (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2022)
This paper reports on research into librarian participation on faculty association executive and collective bargaining teams at 46 Canadian universities at which librarians are in the same bargaining unit as professors. The goal of this study is to determine the extent of such participation on these key committees, whether such participation is mandated by governing documents or a matter of custom (or neither), and what barriers librarians face to such participation. The authors analyzed these associations’ constitutions and bylaws and then conducted interviews with faculty association leaders and librarian activists. Findings indicate that nearly half of the surveyed associations either have a mandated seat for librarians or make every effort to include librarians on their executive committees, and more than a third do the same for their collective bargaining teams. Many associations have had a librarian as faculty association president and a handful have had a librarian as chief negotiator. The most-cited barriers to taking on these leadership roles in the association are workload and the lack of or unsuitability of course release for librarians. The level of librarian participation in faculty associations across Canada is very encouraging, but many issues need to be addressed if librarians are to have a full seat at the table.